Changes of approaches to chemotherapy in children of the tender age over 30-year period - A. R. Аroyan; E. S. Leontievа; A. V. Mordyk (Туберкулез и болезни лёгких, 2018)
The objective of the study: to analyze approaches to chemotherapy in children of the tender age over a 30-year period. Subjects and methods. 390 children of the tender age (0-3 years old) were included in the study, they all were treated in the hospital due to tuberculosis from 1985 to 2014. Children were divided into 6 groups based on the time period (six five-year periods). Results of the study. During different periods of time, changes in the regimens of anti-tuberculosis drugs for children in the age from 0 to 3 years old have been related to the valid regulations, making provisions for chemotherapy principles, and parameters of the drug supply to TB units. The increase in the number of drugs in treatment regimens for children of the tender age has been related to the growing frequency of drug resistant tuberculosis and it has promoted the development of a bigger number adverse reactions caused by the drugs.